Language typology and reconstruction the prenasalized stops of Kisi - G. Tucker Childs (LibraryPress@UF, 1992)
The findings of language typologists can contribute to understanding synchronic variation where no diachronic facts are available. By establishing what happens universally, one can extrapolate as to the past and perhaps as to the future of a language on the basis of synchronic evidence. One approach within such a framework concentrates on a typologically unusual or marked feature on the assumption that its derivation may be established from less highly marked features. This paper discusses the typologically unusual prenasalized stops of Kisi, a Mel language belonging to the Southern Branch of (West) Atlantic. The approach adopted here is based on the process-oriented framework developed by Joseph Greenberg.